Pemahaman Konsep Matematis Dilihat dari Minat Belajar dengan Strategi Pembelajaran Genius Learning Berbantu Lagu Edukasi - Anathiya, Ladika; Netriwati; Andriani, Siska (Circle: Jurnal Pendidikan Matematika, 2021)
The purpose of this study was to determine the effect of Genius Learning Strategies assisted by Educational Songs on understanding mathematical concepts, to determine the influence between students who have high, medium and low learning interest on understanding mathematical concepts. The method used in this research is quantitative with the type of True Experiment Design. The study population was all students of class VII SMP Negeri 1 Sukau, the sampling technique in this study used the random sampling technique where class VII A was the experimental class 1 by implementing the Genius Learning strategy assisted by educational songs, class VII C was the experimental class 2 by applying Genius learning strategies and class VII B as a control class using conventional methods. The instruments used to collect the data were the mathematics concept understanding test and the learning interest questionnaire. The data analysis technique used in this study was the two-way Anova test with different cells. Based on the test results, for the first hypothesis H_0A was rejected because the p-value of the Genius Learning learning strategy assisted by Educational Songs = 0,000 was less than α = 0.05 (p-Value≤α). The conclusion is that there is an effect of the Genius Learning strategy assisted by Educational Songs on the ability of students to understand mathematical concepts.